Development of An Eco-Shampoo Formulation Using Local Environmental Plant Extracts for Healthy Hair as an Effort to Increase the Potential of Environmental Resources - Dwi Atmanto; Neneng Siti Silfi Ambarwati (Biology, Medicine, & Natural Product Chemistry, 2023)
This research aims to develop an eco-friendly shampoo formulation (Eco-Shampoo) by adding local environmental plant extracts for hair health. This research method is a quasi-experimental development of existing shampoo formulations (base formulations) by adding local plant extracts such as aloe vera (Aloe vera L.) and lemongrass oil (Cymbopogon citratus) in three formulations. The resulting shampoo products were then carried out two evaluations, namely the stability test (organoleptic test), foam height observation, viscosity test, pH test, and preference test (hedonic test) by consumers to determine the feasibility and effectiveness of using shampoo. After a storage period of 2 days showed a Stability test, slightly changed color, constant odor, and texture did not change and the pH value was between 5.5 - 6.5. The smear test on the back of the hand and the skin behind the ear did not show skin irritation, whereas the hedonic test, 10 consumers stated that the color was like, the smell was stated like, and the texture was stated quietly. Aloe vera fraction and lemongrass oil can be formulated as a shampoo preparation to maintain hair fertility as well as an anti-dandruff shampoo.